A Problem of Middlebrow Style: Dialect and Translation in Elena Ferrante's Naples Tetralogy. Issue 4 (3rd April 2022) - Robinson, Richard
ABSTRACT: How does the Bakhtinian model of novelistic discourse, which conceives of dialects as styles and styles as dialects, appear in the age of world literature and world English? If the style of the contemporary world-novel is purposely drained of heteroglossia, it risks complicity with a frictionless communicability. This essay argues that, despite its magmatically latent energy, the near-complete absence of napoletano in Elena Ferrante's Neapolitan novels emphasises a refusal both to utter and be uttered by dialectal delinquency. Canonical writers such as Verga, Svevo, Pasolini and Ginzburg had responded to the extraordinary rapidity with which dialects were largely subsumed by spoken as well as written Italian. Yet Ferrante prompts new questions about how the global cultures of reception are gendered. Resisting the masculinist performance of a named style, she pseudonymously embraces the sensibility of the feminised 'middlebrow', a category now conceived as immersive and cognitively complex. Under such conditions, the questione linguistica is confronted in narrative: its evasion in language marks both the constraints and possibilities of pan-feminist translatability in the 'world lit' economy.